Faktor-Faktor Keterlambatan Surat Perintah Perjalanan Dinas Biro Umum dan Rumga Setda Provinsi Jawa Timur - Vony Aliefia; Oktarizka Reviandani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Official travel is carried out by authorized officials to attend invitations, meetings, seminars, and so on, especially in government. Service Travel Order (SPPD) as proof of accountability for carrying out official travel. In working on SPPD, it is not always smooth and timely because there are many obstacles that cause delays which have an impact on the slow disbursement of proposed official travel funds. Researchers used 4 main focuses in the study to determine the factors of SPPD delays, namely (1) Human Resources Factors, (2) Internal Control, and (3) Technology and information factors and. (4) Dominant Factors The research method used by researchers is descriptive qualitative with data collection techniques in-depth interviews, observation, and documentation. The results of this study are (1) Human Resources Factors, have worked quickly in accordance with existing regulations, (2) Internal Control, internal factors still cannot be controlled because the mobility of the leader concerned has a busy schedule resulting in a buildup of files and stagnation of the submission process. External factors can still be followed up by implementers regarding the timeliness of sending invoices, because invoices are the main administrative requirement in SPPD. (3) Technology and Information Factors, which still use manual methods in their work, namely using Microsoft excel, so that a lot of work is not automatic and synchronized between one file and another, (4) Dominant Factors, delays are dominated by the mobility of busy leaders and supporting documents that are submitted late. This problem is a factor in the delay of SPPD